DETERMINANTS OF GOVERNMENT INTERNAL AUDIT QUALITY: FAKTOR-FAKTOR PENENTU KUALITAS AUDIT INTERNAL PEMERINTAH - Sitorus, Laurenza; Wibowo, Puji (Universitas Airlangga, 2025)
This research analyzes the factors influencing the internal audit quality at the BPKP Representative Office of South Sulawesi Province. Using attribution theory, this study explains that the quality of supervision is influenced by both internal and external factors. The internal factors examined are auditor competence and independence, while the external factors include leadership and time budget pressure. This study employed a census sampling method, involving all 105 auditors at the BPKP Representative Office, with 101 auditors returning valid responses. Data were analyzed using SmartPLS 4. The results show that competence, independence, and leadership have a positive and significant influence on internal audit quality, while time budget pressure has no effect. These findings provide valuable insights for improving internal audit quality at BPKP and other APIP agencies, while also contributing to the literature on public sector internal audits in Indonesia